Effects of Drying Methods and Temperatures on the Quality of Chestnut Flours - Veronica Conti; Patrizia Salusti; Marco Romi; Claudio Cantini (Foods, 2022)
The demand for chestnut flour is growing because of its use in gluten-free products. Previous studies have correlated the quality of chestnut flours to the drying temperature and technology applied. This work is a novel study on the role of the traditional drying method with a wood fire in a “metato” building for flour compared with a food dryer at 40 °C or 70 °C. The contents of antioxidants, total polyphenols and sugars were determined as well as the presence of toxic volatiles or aflatoxins. The flour, resulting from the traditional method, presented lower polyphenol content and antioxidant power compared to the others. The content of the sugars was similar to the flours obtained after drying with hot air, both at 40 °C and 70 °C. The toxic volatile molecules, furfural, guaiacol, and o-cresol, were found. There was no correlation between the aflatoxin content and the presence of damage in chestnut fruits. The traditional method should not be abandoned since it confers a pleasant smoky taste to the product, but it is necessary to regulate the level and steadiness of temperature. Future research needs to be directed to the quantification of harmful volatile compounds and their correlation with the quantity of smoke emitted by the wood fire.